Recanalization rate in patients with proximal vein thrombosis treated with the direct oral anticoagulants. Issue 153 (May 2017) - Prandoni, Paolo; Ageno, Walter; Mumoli, Nicola; Zanatta, Nello; Imberti, Davide; Visonà, Adriana; Ciammaichella, Maurizio; Simioni, Livio; Cappelli, Roberto; Bucherini, Eugenio; Di Nisio, Marcello; Avruscio, Giampiero; et al.
Abstract: Background: The recanalization rate in patients with deep venous thrombosis (DVT) of the legs treated with the direct oral anticoagulants (DOAC) is unknown. Methods: In an Italian cohort, we investigated the rate of residual vein thrombosis (RVT) after three and/or six months in 352 patients with proximal DVT who had been treated with the DOACs as a stand-alone therapy or lead-in parenteral anticoagulants, and compared it to that recorded in a historical cohort of 1094 patients in which vitamin K antagonists (VKAs) had been employed. In both cohorts, RVT was defined as the ultrasound persistence of thrombotic material resulting in a diameter of at least 4 mm of incompressibility of the proximal veins. Results: RVT was detected in 143 patients treated with DOACs (41.2%) after three months and in 58 patients (21.1%) after six months; the corresponding figure in patients treated with conventional anticoagulation was 52.3% and 54.5%, respectively. After adjusting for the baseline characteristics, the odds ratio of RVT in patients treated with the DOACs as compared with those treated with conventional anticoagulation was 0.63 (95% CI, 0.48–0.81) after three months, and 0.17 (95% CI; 0.11–0.26) after six months. Conclusions: In patients with proximal DVT treated with the DOACs, the persistence of ultrasound detectable RVT is likely to occur less frequently than in patients treated with conventional anticoagulation. These results may have implications for the prognosis of patients with DVT. Highlights: The recanalization rate in patients with proximal DVT treated with the DOACs is unknown. Residual vein thrombosis is less likely to occur than in patients treated with VKAs. These findings may have implications for the prognosis of patients with DVT.